Contact angle and adsorption energies of nanoparticles at the air–liquid interface determined by neutron reflectivity and molecular dynamics. Issue 13 (6th March 2015) - Reguera, Javier; Ponomarev, Evgeniy; Geue, Thomas; Stellacci, Francesco; Bresme, Fernando; Moglianetti, Mauro
Abstract : A new approach, based on in situ neutron reflectivity and molecular dynamics has been developed for calculating contact angles of nanoparticles at interfaces. Abstract : Understanding how nanomaterials interact with interfaces is essential to control their self-assembly as well as their optical, electronic, and catalytic properties. We present here an experimental approach based on neutron reflectivity (NR) that allows the in situ measurement of the contact angles of nanoparticles adsorbed at fluid interfaces. Because our method provides a route to quantify the adsorption and interfacial energies of the nanoparticles in situ, it circumvents problems associated with existing indirect methods, which rely on the transport of the monolayers to substrates for further analysis. We illustrate the method by measuring the contact angle of hydrophilic and hydrophobic gold nanoparticles, coated with perdeuterated octanethiol (d-OT) and with a mixture of d-OT and mercaptohexanol (MHol), respectively. The contact angles were also calculated via atomistic molecular dynamics (MD) computations, showing excellent agreement with the experimental data. Our method opens the route to quantify the adsorption of complex nanoparticle structures adsorbed at fluid interfaces featuring different chemical compositions.